STRATEGIES TO ENHANCE OCCUPATIONAL HEALTH AND SAFETY ACCOUNTABILITY IN MUSI BANYUASIN REGENCY - Lionardo, Andries; Syafebri, Arrahman; M. Saleh, Hatta; Adam, Ryan (Iapa Proceedings Conference, 2025)
Occupational Health and Safety (OHS) accountability has increasingly become a cornerstone of sustainable labor governance, particularly in developing regions where informal and part-time employment structures dominate. In Indonesia, despite an extensive regulatory framework including Law No. 1 of 1970 on Occupational Safety and Government Regulation No. 50 of 2012 on OHS Management Systems (SMK3) implementation remains inconsistent, with accountability mechanisms still weak at both institutional and behavioral levels. This study aims to formulate a strategic framework to enhance OHS accountability in Musi Banyuasin Regency, South Sumatra, as a representative industrial area facing rapid employment transformation. Using a mixed-method design, the research integrates quantitative labor market data (2020–2024) with qualitative interviews involving key government, industry, and labor stakeholders. Quantitative findings reveal persistent gender disparities in employment and a high share of part-time labor, indicating fragility in OHS compliance and risk management. Qualitative analysis identifies fragmented inter-agency coordination, limited safety literacy, and underdeveloped digital reporting mechanisms. The study proposes a collaborative governance- based model emphasizing digitalized reporting, inter-institutional data integration, and community-centered safety literacy enhancement. This model extends the theoretical discourse on accountability by bridging the gap between regulatory compliance and moral responsibility. The findings contribute to the literature on safety governance by conceptualizing accountability as a multidimensional construct that intertwines institutional transparency, behavioral commitment, and procedural enforcement. Practically, the paper provides a roadmap for strengthening OHS accountability through policy innovation and technology adoption, aligning local governance reform with the broader Sustainable Development Goals (SDG 8.8) on safe and secure working environments.